Boron nutrition, intracellular transport, and knife-cut disease in sunflower - Fuertes, M. E. (2010)
The present study was conducted to investigate in sunflower the processes of boron (B) uptake, intracellular compartmentation, and xylem translocation in response to B supply, ranging from deficiency to incipient toxicity, and to short-term changes in B supply. The experiments were conducted with two sunflower genotypes, selected on the basis of their susceptibility to knife-cut disease. It appears that the roots of the susceptible genotype of sunflower were more sensitive to low B contents in the solution media than the shoots. The decrease in root dry weight in high-B treatments could also indicate it was more sensitive to B toxicity. Though root dry weight decreased, the shoot/root dry-weight ratio was smaller in the resistant genotype, suggesting that this genotype would have a substantially larger root volume, capable of supporting the B demand of its shoots. The B contents in the water-insoluble residue (WIR) of roots were similar for all genotypes and treatments. In contrast, the B concentration in WIR of leaves reached values near saturation only when B started to accumulate in the cell sap (CS) of roots to the level as detected in CS of leaves. The critical values of B concentrations in shoot tissues would then be established after the B requirement for cell walls was satisfied and a proper metabolic B content in CS of roots was reached. Uptake efficiency (UE) values less than 1.00, detected as a result of treatments with high concentrations of B in the nutrient solution, suggested the presence of an exclusion mechanism that restricted B accumulation. The high UE value obtained with low-B treatments indicated that mechanisms other than mass flow had played a role in providing the acquired B.